Socio-demographic and clinical factors associated with relapse in mental illness - Munirat Olayinka Adebiyi; Samuel Kolawole Mosaku; Omolola Oladunni Irinoye; Oyeyemi Olajumoke Oyelade (Elsevier, 2018)
Purpose: Relapse in mental illness is an issue of concern to both the patients and caregivers. This study primarily focused on determining the rate of relapse and identifying the socio-demographic and clinical factors associated with relapse. Method: A 5 year retrospective study was done involving 219 clients admitted into a mental health care facility in Nigeria. A proforma was designed to collect data on the socio-demographic and clinical variables from the client's case notes after obtaining ethical clearance. Data was fed into SPSS version 16 and analysed using univariate and bivariate statistic. Findings: Multiple logistic regression was performed to ascertain the effect of age at onset of illness, living arrangement, family background, social class, index employment status, educational status, duration of illness and drug compliance on the likelihood of relapse in mental illness. The model was statistically significant, X2 (24) = 69.52, p < .0005, explained 36.7% (Nagelkerke R2) of the variance in relapse and correctly classified 74% of the cases. Those with duration of illness greater than five years were 3.43 times more likely to relapse than those with lesser years. Lower age of onset predicts 2.76 times more likelihood of relapse but being employed at the onset of the illness and compliance reduces the likelihood of relapse. Conclusion: This study concluded that socio-demographic and clinical factors were significantly associated with relapse. Addressing these will help achieve sustainable development goals for this population of patients. Keywords: Relapse, Readmission, Clinical factors, Socio-demographic factors, Drug compliance